Analisis Dampak Dual Banking System Bank Indonesia terhadap Volume Pembiayaan Berprinsip Syariah di Indonesia - Nugroho, Muh Rudi; Rokhaniyah, Siti (Manajemen Bisnis Syariah, 2011)
The study entitled "Analysis of Dual Banking System Bank Indonesia against Shariah financing principles in Indonesia", using the data time series that began in 2003 fourth quarter. Research was conducted to analyze the factors that affect the volume of financing in Islamic Banking among others: deposits, bank capital, the number of bank offices, and inflation. In addition the dual banking system implementation of the policy of Bank Indonesia.   The study was conducted to determine how much influence policy dual banking system, third-party funds (TPF), capital of banks (MDL), the number of bank offices (JKB), and inflation (INF) in the short and long term financing to the debt based on sharia principles in Indonesia.   These quarterly data analysis using OLS regression (Ordinary Least Square) with the approach Partial Adjustment Method (PAM). This model was chosen to comply with the regression technique is used where data should show a stationary trend. This is done so that the results are not misleading the development of economic variables on which most of the time of crisis is very volatile, so it is possible that the data has not stationary.This is based on the assumption that economic conditions in the imbalance. Before performing regression PAM first performed model selection, the test unit roots, cointegration test, t test, F test, test R2, as well as the classic assumption test. Based on the PAM test results that in the short term, all the variables together significantly influence the volume of financing based on Islamic principles in Indonesia.The amount of financing amounting to 5483 million dollars is affected by the dual banking system, deposits, MDL, JKB, and INF. If deposits increased 1% the volume of financing will increase by 0489%. The volume of financing will increase by 0378%, if the MDL rose 1%, so if inflation rises by 1%, the volume of financing will go up 0007%. Testing the PAM model shows the magnitude of the adjustment coefficient 1 - δ (1-0.172070 = 0.82793). This shows that 82.79% is the differences between the actual financing with financing have been achieved in one period. With the value of this coefficient, shows that in the long run, each coefficient is greater than the coefficient in the short term. Volume of financing in the long run is 6623 million dollars regardless of the dual banking system, deposits, MDL, JKB, and INF. Long-term value of elastic coefficient of each variable is; DPK = 0590 (inelastic), MDL = 0457 (inelastic), JKB = 0088 (inelastic), INF = 0008 (inelastic), and Dummy = -0007 (inelastic). Advice given in this study, among others; Bank Indonesia in implementing and developing the dual banking system while maintaining the strict sharia, in addition to that necessary to disseminate Islamic Bank more effectively and continue to the wider community. Islamic banks have to strengthen the capital side, raising third party funds and optimize the functions of the office network to increase the volume of financing and Islamic Banks should implement strict risk management in the distribution of financing. Keywords: Dual Banking System, Partial Adjustment Method, and Sharia Banking